Long-term outcomes of per-oral endoscopic myotomy in a patient with distal esophageal spasm followed up for 2.5 years: two sides of the same coin – A Case Report and Literature Review - Wang, Bin; Jin, Hong; Zhao, Wei; Zhao, Chunshan; Wang, Tao; Zhang, Lili; Sun, Fangyuan; Wang, Bangmao; Song, Jiye (Zeitschrift für Gastroenterologie, 2019)
Introduction Distal esophageal spasm (DES), a relatively rare condition, is characterized by simultaneous contractions of the distal esophagus and manifested by dysphagia and chest pain. Several treatment options are recommended, such as pharmacological therapy, endoscopic interventions, and surgical myotomy. Recently, per-oral endoscopic myotomy (POEM) has been adopted as an effective and less-invasive treatment due to its excellent short-term clinical outcomes. Nevertheless, few reports describe its long-term effects.Case presentation A 65-year-old woman complained of chest pain accompanied with dysphagia and weight loss for 4 months. A series of examinations suggested that she was suffering from DES and then POEM was performed. During the 2.5-year follow-up, we observed an exciting long-term outcome. Interestingly, hematoxylin and eosin staining verified a large number of eosinophils in the muscularis externa, which was absent in the mucosa of the esophagus of the patient.Conclusions We herein report a case of DES who underwent POEM to eliminate persistent esophageal contractions. Eckardt score, esophageal emptying test, and high-resolution manometry were assumed to monitor the efficacy of POEM. During treatment and 2.5 years after operation, esophageal muscle biopsies and/or mucosal tissues were obtained. This case has been presented to describe that POEM could be a strategy for DES with a long-term curative effect and that eosinophils in the muscle layer of the esophagus might be involved in the pathogenesis of DES. What is more, we reviewed literature to find similar cases reported in the past.
Keywords: distal esophageal spasm; per-oral endoscopic myotomy; eosinophils